La necesidad de un curso de evaluación adaptado al Bachillerato en Educación Primaria con Concentración en Inglés en la Universidad de Costa Rica - María Antonieta Vargas Solís; Carolina Álvarez Fuentes (Universidad de Costa Rica, 2020)
Between the years 2014 and 2015 researchers started to work as supervisors in the teaching practicum. From that point on, every year they noticed that the student-teachers struggle regarding how to assess English at the elementary school level. Since students from the Bachelor "Elementary Education with a minor in English" already take an evaluation course, researching the reasons for that weakness was key to better support our students. That is why this article presents the results of the qualitative research carried out in 2016 aiming to explore the need for designing an evaluation course taught in English and tailored to the students enrolled in the Bachelor "Elementary Education with a minor in English" at the University of Costa Rica, Western Campus. Through the use of an exploratory and phenomenological design, the researchers interviewed thirteen student-teachers, nine former students from this bachelor, an experienced elementary school teacher, and two authorities from the Ministry of Public Education of Costa Rica (MEP) to obtain their perspectives about the course ED0196 "Evaluation of the Learning Process in Early Childhood and Primary Education." Also, the syllabus of the course was analyzed based on what students must know to assess a foreign language. Data showed that although students learn about many instruments and assessment criteria, many of them are not tailored to assess English as a Foreign Language but other core subjects. Based on the findings, the researchers concluded that the course ED0196 does not meet the needs of these students, and therefore, the university needs to design a course specifically tailored for them.